La interculturalidad en el desempeño académico y social de los estudiantes del cuarto semestre de la Carrera de Mecánica Automotriz del Instituto Superior Tecnológico Carlos Cisneros. - Buenaño Llerena, Carlos David (2025)
This research work, entitled "Interculturality in the Academic and Social Performance of Fourth-semester Students of the Automotive Mechanics Career at the Higher Technological Institute Carlos Cisneros," deals with the influence of interculturality on students' academic performance and social integration. The main objective of this investigation is to analyze the impact of interculturality on the academic performance and social integration of fourthsemester students of the Automotive Mechanics career. A mixed methodology approach was applied in the field investigation conducted in the Higher Technological Institute "Carlos Cisneros." Furthermore, a bibliographic modality was used, and the conceptual review was carried out in books and digital documents, enforcing the exploration and descriptive method. Forty-two people involved in the research were worked on; data collection was carried out using observation, survey, and interview techniques. The code of institutional coexistence and the management of teachers for peaceful conflict resolutions are identified as strengths; weaknesses are traditional teaching methodology based on master classes, teaching-learning strategies focused on monthly group assignments and weak enforcement of collaborative work techniques that allow social integration among students. The strengthening of cultural identity has not been promoted. Based on these findings, the proposed methodology to strengthen the teaching-learning process is based on applying collaborative work techniques, which will encourage participation in student training and social coexistence.